Photochemische S-Eliminierung aus 2,11-Dithia-[3]metacyclo[3](3,5)pyridinophan - J. Bruhin; W. Kneubühler; W. Jenny (CHIMIA)
The synthesis of [2]metacyclo[2](3,5)pyridinophane by photochemical extrusion of sulfur from 2,11-dithia-[3] metacyclo[3](3,5)pyridinophane in a trivalent organophosphorus solvent is described. As intermediate 2-thia-[3]metacyclo[2](3,5)pyridinophane was isolated.